DISTRIBUSI PARASIT USUS PROTOZOA DI KABUPATEN HULU SUNGAI UTARA KALIMANTAN SELATAN - Anorital, Anorital; Dewi, Rita M.; Ompusunggu, Sahat (Media Penelitian dan Pengembangan Kesehatan, 2010)
The intestinal infection disease caused by protozoa: amoeba is one of the public health problem with high incidence in the community. From the research activity conducted in Hulu Sungai Utara Regency in the year 2002, to obtain of prevalence of protozoa infection from stool examination from resident in 6 villages at 3 subdistrict in Hulu Sungai Utara Regency. The research has conducted to be carry out survey parasite to the community. Sample size will be examination are 230 persons per village, so that to 6 villages will be examed as 1.600 persons. The examination directly by using lugol 2% and checked on the microscope with magnification 10x10 and 10x40. For resident which its sample stool is positive the protozoa to be given a treatment by metronidazol. From stool examination result obtained prevalence resident which are positive the amoeba intestine protozoa is Entamoeba coli 19,8%, Endolimax nana 15,8%, and Entamoeba histolityca 15,4%. While prevalence resident which are positive the intestine flagellata/B. hominis is Blastocystis hominis 25,5% and Giardia lamblia 11,6%. From 5 micro-organism on the intestine. Entamoeba histolityca, Blastocystis hominis and Giardia lamblia are cause diarrhoea because having the pathogenic. From survey ot socio-cultural, known also the resident percentage which drinking no safe water 43,3%, source of drinking water obtained from river or swamp is 67,7%, human waste disposal in river and swamp is 79,5%, and take a bath and brush the teeth with water of river and swamp is 78,6%; showing bad condition of environmental sanitation, personal hygiene, and life behavior. Good personal hygiene and environmental sanitation practices are the major factors of this disease prevention. The main principle to prevent the spreading of protozoa infection is to cut off the link of infection sources to human beings. Personal hygiene is focused on the management of individual behaviour, meanwhile environmental sanitation prevention focus lies on the better environment management to cut off the link of disease cycle as like water supply and human waste disposal wich good condition. For this matter is Governmental role, in this case the health office and with local elite figure, important and absolute so that to a period to coming of prevalence intestine infection caused a protozoa can be depressed as low as possible.   Keywords: protozoa